Revisiting the decentralization theorem: on the role of externalities - Marko Koethenbuerger (Center for Economic Studies and ifo Institute (CESifo), 2007)
The Decentralization Theorem (Oates, 1972) is central to the discussion of fiscal federalism. We revisit the role of consumption spillovers in evaluating the merits of (de)centralization. Unlike the general prediction, a higher degree of spillovers may reduce the difference in utility of centralization and decentralization. The non-monotonicity result relates to the difference in expenditures on public consumption. Provided decentralized choices yield higher levels of public expenditure, a rise in the amount of spillovers allows residents to enjoy larger gains in public consumption (and thereby utility) under decentralization relative to centralization.
Keywords: H10; H30; H70; 330; federalism; decentralization theorem; externality; policy uniformity; Finanzföderalismus; Externer Effekt; Dezentralisierung; Öffentliches Gut; Gesamtwirtschaftlicher Konsum; Spillover-Effekt; Föderalismus; Wohlfahrtstheorie; Theorie